Interdictal possession, right of possession independent of ownership, and right to possess - Chacón Bravo, Francisco (2025)
For us, the Costa Rica Civil Code considers possession as a right, which includes the right to interdictal protection, the right to independent possession of property for more than one year, and the right to possess with different meanings.